TINJAUAN KRITIS TERHADAP WACANA GLOBAL GOVERNANCE DALAM UPAYA PERLINDUNGAN PEKERJA MIGRAN INDONESIA - Rengga Dina Permana (UNIDA Gontor, 2021)
Discourse of Global Governance came along with globalization. This article will not showing reader about the debates among scholars regarding the wide definition of globalization, rather this article is a production of critical consciousness. Using Foucault’s governmentality in order to dismantle the technology of power this article explains how then globalization with the issues that came along with its discourse.In this case I raise human rights issue that becoming the political rationalization of protecting of migrant worker must be started from human rights discourse and take it as the regime of truth.